Profil Pasien Ketoasidosis Diabetikum di Rumah Sakit Rujukan Tersier di Bali, Indonesia - Joenputri, Noviana, NJ; Suastika, Ketut, KS; Gotera, Wira, WG; Saraswati, Made Ratna, MRS; Dwipayana, I Made Pande, IMPD; Semadi, I Made Siswadi, IMSS; Nugraha, Ida Bagus Aditya, IBAN (Jurnal Penyakit Dalam Indonesia, 2023)
Introduction. Diabetic ketoacidosis (DKA) is one of life-threatening acute complication of diabetes mellitus (DM) characterized by hyperglycemia, ketosis, and acidosis. The prevalence of DM is increasing, therefore the incidence of DKA is predicted to continue to increase. The aim of this study was to obtain the profile of DKA patients in RSUP Prof. Dr. IGNG. Ngoerah (RSPN), Denpasar, Bali as a tertiary refferal hospital of Bali and Nusa Tenggara region. Methods. This study was a cohort retrospective study. All patients aged 18 years or older with a diagnosis of DKA during Januari 2022 to February 2023 at RSPN, were included in this study. Data were obtained from medical records then analyzed using the SPSS version 26 program. Results. There were a total of 41 patients with DKA with mean of age was 50,59 (SD 16,87) years, most of them were female (51,2%) and came alone without referral (58,5%). Based on the clinical profile, most patients presented with decreased consciousness (36,5%), infection (90,2%) mostly urinary tract infection (UTI) (40,5%), have a history of insulin use (34,1%), and impaired of renal function (85,4%). The mean of blood glucose was 468,95 (SD 207,78) mg/dL, potassium level 4,19 (SD 1,17) mmol/L, bicarbonate level 12,85 (SD 6,27) mmol/L, and HbA1c 11,5% (7,1-14). The median duration of hospitalization was 7 (1-30) days and 19,5% of them were passed away during treatment, mostly within the first 72 hours. Conclusions. Most patients in this study are female with age less than 60 years. The most common precipitating factor of DKA are UTI and poor glycemic control. A total of 19,5% of patients with DKA were passed away in this study. Thus, clinicians should be more aggressive in the management of DKA, particularly in the first 72 hours.